Enhancement of Cassava Productivity by Adopting Integrated Crop Management Practices in Tamil Nadu: A Case Study - Malarkodi, M; Ravi, M (JOURNAL OF ROOT CROPS, 2017)
Front Line Demonstrations (FLD) on integrated crop management practices including sett treatment with carbendazim 2 g litre -1 , application of micronutrient mixture @ 12.5 kg ha -1 ; release of Acerophagus papayae parasitoid @ 100 numbers ha -1 and foliar spaying of 1% FeSO 4 and 0.5% ZnSO 4 on 60 and 90 days after planting to manage papaya mealy bug and micronutrient deficiency in cassava were conducted at 15 farm holdings (1 acre per farm) in Tiruchirappalli district, Tamil Nadu during 2011. The results revealed that the average storage root yield of 34.5 t ha -1 was recorded in demonstration plot which was 20.7% greater than the check plot yield. On an average, 6.61 storage roots per plant were recorded in demonstration plots whereas 5.46 storage roots per plant were recorded in check plot. On an average, farmer earned an additional net income of Rs. 16,700/- by adopting the improved technologies. The infestation of papaya mealybug was reduced by 72% compared to control due to parasitization of Acerophagus papayea.